The Effects Of Clinical Supervision Of Academic Model To Improve The Ability Of Nurses In Applying Patient-Centered Care (PCC) At Hospital - Arifin Dwi Atmaja; MC Inge Hartini; Luky Dwi Antoro (NURSCOPE: Jurnal Penelitian dan Pemikiran Ilmiah Keperawatan, 2018)
Introduction: Quality patient centered care will improve the quality of nursing care and the patients independence, life quality, and self-efficacy. It also reduces the rate of disease recurrence, the length of stay (LOS), and the cost of care. Clinical supervision of academic model is a method to increase professionalism in the delivery of nursing care. The purpose of this study was to determine the effects of clinical supervision academic model of head nurses on the quality of discharge planning. The study represented a pre-post test quasi-experimental design with a control group. The population was all nurses in Mitra Siaga hospital. The samples were 51 nurses selected by non-probability sampling. The statistical analysis used was one-way ANOVA. The results showed that the clinical supervision of academic model of the head nurses had a significant effect on improving the ability of nurse in applying patient centered care. Clinical supervision of academic model is a competence that nursing managers should have; therefore, it is suggested that head nurses provide guidance and supervision continuosly to maintain and improve the quality of patient centered care.